Has the Rate of Investment Fallen? - Feldstein, Martin (The Review of Economics and Statistics, 1983)
Although the ratio of gross fixed nonresidential investment to GNP has decreased very little since the late 1960's, the corresponding net investment ratio declined by nearly 40 percent between the second half of the l960's and the second half of the 1970's. Four-fifths of this decline was due to the increased ratio of depreciation to GNP and only one-fifth to the decreased ratio of gross investment to GNP. The increased ratio of depreciation to GNP was in turn due in equal amounts to the higher ratio of capital to GNP and to the higher rate of depreciation. Nearly half of the higher depreciation rate was due to the increased rate of depreciation of equipment and nearly half to the increased share of equipment in the capital stock.